ANALISIS DAYA TARIK WISATA DI DEPATI VII COFFEE KOTA SUNGAI PENUH - Dini, Diva Permata; Martina, Elti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This research is motivated by the lack of scientific research on the elements that form the tourist attraction of Depati VII Coffee as a popular tourist attraction in Sungai Penuh City. In addition, there are still aspects of tourism that need to be arranged and developed to suit the concept of cultural and educational tourism that is carried out. This study aims to analyze the tourist attractions of Depati VII Coffee based on the experiences and perceptions of visitors, as well as identify the factors that contribute most to the attraction of the destination. The research uses a qualitative approach with a descriptive method. Data was collected through in-depth interviews, field observations, and documentation, then analyzed through the process of reduction, data presentation, and conclusion drawn. The results of the study show that the attractiveness of Depati VII Coffee is formed from a combination of tourist activities, natural beauty, distinctive products, regional aesthetics, and supporting facilities. Social activities, recreation, and education are the dominant attractions that provide a complete experience for visitors. Natural beauty such as a beautiful atmosphere, cool air, and expanse of coffee gardens also strengthen the comfort of tourists. Local coffee products are a distinctive identity that distinguishes Depati VII Coffee from other destinations, while adequate facilities support the smooth running of tourism activities even though there are still shortcomings such as limited shelters and internet networks. Overall, Depati VII Coffee has a comprehensive appeal that reflects a combination of natural elements, education, culture, and visitor experience. Strengthening aspects of cultural identity and education is needed so that this destination can develop more optimally. Keywords: Tourist Attractions, Natural Tourism, Visitor Perception, Depati VII Coffee, Sungai Penuh City